JOURNALISM ON SOCIAL MEDIA: BETWEEN FREEDOM AND RESPONSIBILITY - Tokhirova Sevinch Akram kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Social media has revolutionized the way journalism functions by creating new platforms for information sharing, public discourse, and engagement. However, this transformation also brings significant ethical, professional, and social challenges. This article examines the evolving relationship between journalism and social media, focusing on the balance between the freedom of expression and the responsibility to ensure accuracy, fairness, and accountability. It explores how journalists navigate the digital environment, the risks of misinformation, and the impact of social platforms on journalistic integrity and democratic values.